Portal hypertension presenting with gastroesophageal varices in children: Causes, Management and Outcome / Nithia Kamala Athimoolam - Nithia Kamala, Athimoolam (2017)
It has always been a challenge to manage portal hypertension presenting with gastroesophageal varices in children. The aetiologies of portal hypertension in children differs from adults, however due to a lack of paediatric data, much of current practice in children is adapted from adult guidelines. This study describes a local population of children with portal hypertension presenting with gastroesophageal varices seen in a tertiary referral centre in Malaysia. Retrospective descriptive cohort study analysing data from medical records of paediatric patients with endoscopy finding of gastroesophageal varices from l51 December 2000 to l51 December 2016 was conducted. A total of 38 patient's records were analysed. The study population of38 patients were made up of 18 Malay patients (47.3%), 17 Chinese patients (44.7%), 2 patients of other ethnicity and one Indian. The gender distribution was equal. A total of 22 out of 38 patients (57.8%) had intra-hepatic aetiology of portal hypertension, which included 14 patients with biliary atresia. Seven patients (18.4%) had prehepatic aetiology of portal hypertension, of which 6 patients had portal vein thrombosis. Splenomegaly was the most common clinical finding at presentation in 35 patients (92.1 %), and hematemesis was the most common presenting symptom in 19 patients (50%) in this study population. The average age of patients at first endoscopy was 6.72 years (95% CI 5.41 years-8.47 years). Thirty out of 38 patients (78.9%) had intervention with endoscopic variceal band ligation (EVL) or endoscopic sclerosant therapy (EST) in their first endoscopy. In the present study, most of the endoscopies performed were reactive to bleeding events. Bleeding event-driven endoscopies were done in 57.9%, 22 out of 38 patients, while in 16 out of38 patients (42.1 %) endoscopies were performed prophylactically (non-event driven). EVL was used in 21 out of 38 patients while EST was done in 7 patients. Two patients received both EST and EVL. A total of 5 patients out of38 patients (13.2%) encountered complications and the most frequent complication was haemorrhage in 4 patients. Eleven patients had rebleeding after endoscopy. The average bleed-free interval was 87 days (95% CI 42 days-135 days). Shortest bleed-free period post-endoscopy was 12 days. Good bleeding control with more than 5 days interval between endoscopy and rebleeding was observed in this study. Twelve out of 38 patients (31.6%) were still on periodical endoscopic surveillance. Five patients (13.2%) died in this study period. Four patients had liver transplant at average age of8.46 years (95% CI 3.68 years-13.37 years). The comparison between event-driven and non event-driven groups found higher grade varices (p=0.01) and increased intervention rate (p=0.04) in the event-driven group. There was no statistically significant difference seen in age, biochemical parameters, rebleeding events or complication rates between these two groups. In conclusion, the population demographic and aetiology of portal hypertension that presents with gastroesophageal varices in children resembled those in literature (Ng et al., 2016). Splenomegaly and hematemesis remain the most consistent finding at presentation of those patients with gastroesophageal varices. Evaluation of endoscopic outcome by evaluation of complication, rebleeding rate and bleed-free days document safe practice and good efficacy at bleeding arrest. However further research is needed to ascertain the role of endoscopy for surveillance before bleeding event. This study highlighted the endoscopic practises for gastroesophageal varices complicating childhood portal hypertension in University Malaya Medical Centre. This provides a framework for future research on paediatric portal hypertension in our local population.